MODIFICATION OF PRODUCTIVE DOWRY AS A STRATEGY FOR ECONOMIC EMPOWERMENT AND DOMESTIC VIOLENCE PREVENTION FOR WOMEN IN KABUPATEN LOMBOK TENGAH - Munawirsazali, Munawirsazali; Suparlan, Suparlan; Ulia, Simayatul (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2026)
ABSTRACT: This study examines the Modification of Productive Dowry as a Strategy for Economic Empowerment and Domestic Violence Prevention for Women in Central Lombok Regency. The research was conducted due to the urgent need to enhance women's economic independence in Central Lombok, where Domestic Violence in Central Lombok Regency often stems from women's economic dependence, making empowerment through productive dowry in the form of rice fields a potential strategy to enhance financial independence and break the cycle of violence. This qualitative research with an anthropological approach employs field research methods, interviews, observations, and documentation in Central Lombok, analyzed using the interactive model of Miles and Huberman. Findings indicate that productive dowry increases family income, supports children's education, and reduces Domestic Violence risks through economic independence, aligning with Islamic teachings and local wisdom. However, internal challenges (low technical farming skills and financial management) and external ones (patriarchal norms and difficult land locations) hinder optimization. Modification strategies include technical training, financial literacy, and diversifying dowry into business capital to strengthen women's empowerment. This study contributes to reinforcing social capital based on local culture for Domestic Violence prevention.